The Impact of Supply Chain Risk Management on Financial Performance: Evidence from the Southeast Asian Manufacturing Sector - Ming Sheng Fang (Advanced Business Journal, 2026)
Supply chain risk management (SCRM) represents a fundamental priority for industrial enterprises, especially within Southeast Asian markets where heightened globalization and systemic volatility create formidable hurdles. Maintaining operational stability and securing superior financial results necessitates the integration of effective SCRM frameworks. Despite this necessity, scholarly evidence documenting the correlation between SCRM implementation and financial outcomes within this specific geographical context remains sparse. This investigation explores the influence exerted by supply chain risk management on the fiscal health of Southeast Asian manufacturing firms, offering a deeper understanding of how these practices bolster both profitability and organizational endurance. Quantitative research framework was adopted, drawing upon survey data harvested from 250 manufacturing entities operating throughout the region. Structural equation modeling (SEM) served as the primary analytical tool to evaluate the pathways between SCRM activities and key financial performance metrics, including return on assets (ROA) and net profit margins. Results indicate that proficient SCRM practices—specifically risk identification, comprehensive assessment, and proactive mitigation—yield substantial improvements in financial standing. Enterprises equipped with sophisticated SCRM systems demonstrated elevated profitability levels alongside a more robust capacity to withstand external disruptions. Mitigation strategies, most notably, emerged as the most significant driver of positive financial performance. Such findings underscore the critical requirement for adopting holistic SCRM protocols to optimize economic returns within the manufacturing industry.